Extinção da punibilidade dos crimes tributários pelo pagamento: uma crítica à luz do estado democrático de direito e da teoria do bem jurídico - Xerez, Hugo Vasconcelos (2015)
This study analyzes the foundations on which is based the extinction of criminal liability in tax crimes because of payment, to adopt the position against the solution approved by brazilian law, understanding that to allow the extinction of criminal liability because of payment at any time, from taxes previously withheld, the national legislature focuses on a number of legal inconsistencies, especially the insufficient legal good protection safeguarded by these criminal offenses. Therefore, at first it will be made a study on the evolution of the various dimensions of State over the centuries, culminating in the rise of the Democratic State and its close ties with fundamental rights, the principles of social justice and equality and the Criminal Law. Then, once established the inseparable link between the Democratic Rule of Law and the Criminal Law, emphasizing specially the damage that tax evasion causes to the brazilian society, it will be to define the current stage of the legal good theory, according which the foundation of the punitive intervention must be extracted from the values and interests enshrined in the Federal Constitution. After this, the discussion on the legal good safeguarded by tax crimes will be addressed by confronting the patrimonial and functionalist models, concluding for a reconciled solution in which aspects of the two models are adopted. Finally, it will discuss specifically the extinction of criminal liability because of payment in tax crimes, highlighting the historical evolution of the institute in the brazilian legislation, the comparison with the legal choices in other countries, the criticism addressed to brazilian regulation, ending with the proposal of the reinvigoration of a final term for the payment has the power to extinguish the criminal liability of these criminal offenses.